Developing Learning Environment Using Interactive Multimedia - Muhammad Shahzad, Muhammad Asif Nadeem, Zaib U-Nisa (PJDOL, 2021)
The study was conducted in three phases that is testing, using multimedia and observation of the controlled group. Major objective of the research were to assess the implications of software development design on learners and to identify effects of interactive multimedia environment on learning patterns of learners’ at graduate level.